Ham Tourism in Andalusia: An Untapped Opportunity in the Rural Environment - Millán Vázquez-de-la-Torre, Genoveva; Sánchez-Ollero, José Luis; Dancausa Millán, Genoveva (MDPI, 2022)
Iberian ham is a food product of great quality endorsed by Protected Denominations of Origin, which is beginning to be marketed as a tourist product, and visits to pastures, ham dryers, etc., are becoming tourist attractions in the rural areas of Andalusia. In this research, a factor analysis with VARIMAX rotation is carried out to determine the factors that inﬂuence the development of ham tourism. Five components are determined, of which the supply factor is one of the most important. Pull factors are highlighted as the local gastronomy and heritage, among others, and push factors include visiting dryers, pastures, and ham museums. Based on these results and the descriptive analysis of the proﬁle of the ham tourist, it is found that the ham tourist is very satisﬁed with the visit made, and that the tourist would repeat the experience. However, it is observed that it is necessary to create routes combined with other better known gastronomic products, such as wine, and carry out marketing campaigns to publicize this tourist product in the national and international market, because at present it is local tourists who perform this type of tourism.
Keywords: Turismo - Andalucía; Iberian ham; Andalucia; Gastronomic Tourism; Factor analysis